2004
DOI: 10.1158/0008-5472.can-03-3226
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of β-Galactosidase Activity Using Far Red Fluorescent Switch

Abstract: Abstract␤-Galactosidase (␤-gal) has been widely used as a transgene reporter enzyme, and several substrates are available for its in vitro detection. The ability to image ␤-gal expression in living animals would further extend the use of this reporter. Here we show that DDAOG, a conjugate of ␤-galactoside and 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one) (DDAO), is not only a chromogenic ␤-gal substrate but that the cleavage product has far-red fluorescence properties detectable by imaging. Importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
135
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(135 citation statements)
references
References 21 publications
0
135
0
Order By: Relevance
“…Hybrid gene constructs in which either the luciferase or the GFP gene is placed under control of an inducible promoter responsive to a signaling pathway of interest have been used to directly assess the effects of antitumor agents on the gene regulation in vivo. A similar reporter system that directly images β-galactosidase activity on a farred substrate has been recently reported [64]. This fl uorescent reporter system could provide a means for creating hybrid expression units to examine in vivo gene expression and regulation of a number of important pathways in cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Hybrid gene constructs in which either the luciferase or the GFP gene is placed under control of an inducible promoter responsive to a signaling pathway of interest have been used to directly assess the effects of antitumor agents on the gene regulation in vivo. A similar reporter system that directly images β-galactosidase activity on a farred substrate has been recently reported [64]. This fl uorescent reporter system could provide a means for creating hybrid expression units to examine in vivo gene expression and regulation of a number of important pathways in cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, 18-fluoro-L-thymidine uptake may be falsely low if cell cycle arrest is reversible. However, combining these imaging agents with other methods such as measurement SA-b-gal activity (Tung et al, 2004;Liu et al, 2007) and cell death (Al-Ejeh et al, 2007, 2009Thierry et al, 2009) can be used to monitor accurately the status of tumors, for example, in response to DNAdamaging chemotherapy. 'Certainly, mouse models of cancer have been used to address genetics of tumorigenesis for years, but they have been understudied as experimental platforms to investigate short-and long-term consequences of druginducible effector programs' (Kilic and Schmitt, 2008).…”
Section: Assessment Of Therapy-induced Responses In Animal Modelsmentioning
confidence: 99%
“…Water and biological tissues have minimal absorbance and autofluorescence in the NIR window (650-900 nm), thus allowing efficient photon penetration into, and out of tissue with low intra-tissue scattering. Recent advances in the field of molecular imaging have demonstrated that this technology can be used for monitoring the biological activity of a wide variety of molecular targets such as intracellular enzymes (6)(7)(8)(9)(10), cell surface receptors (11)(12)(13)(14)(15)(16), and antigens (17)(18), as well as other targets (19)(20), providing a unique opportunity to achieve insight into the biological events involved with these molecules of interest. Moreover, NIR optical imaging technology is a highly sensitive imaging modality, which does not require use of ionizing radiation or radioactive materials (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%